Vzroki za ishemijo srčne mišice pri bolnikih z visokim krvnim tlakom in hipertrofijo levega prekata - Starc, Radovan (Medicinski razgledi, 2000)
The author discusses the causes of myocardial ischemia among patients with arterial hyper tension and left ventricular hypertrophy. Epidemiological data show that 19% of the Slovene population between the ages of 40 and 70 years suffer from arterial hypertension and almost 80% of such patients die due to left ventricular hypertrophy, myocardial ischemia or their consequences. The multifactorial etiology of myocardial ischemia is analysed and discused systematically and for clinical purposes.
Keywords: hipertenzija; Hypertrophy, left ventricular; ishemija; Hypertension; etiologija; Myocardial ischemia; Etiology